Studi Eksperimental Pengaruh Jumlah Katup Buang Terhadap Kinerja Pompa Hidram - Djaman; Berthy Pelasula; Victor D Waas; Ari Permana L (Journal Mechanical Engineering, 2026)
A hydraulic ram pump is a water pumping device that utilizes the potential energy of flowing water through the water hammer phenomenon without requiring external energy sources such as electricity or fuel. This technology has considerable potential as a sustainable and cost-effective solution for water supply in rural and remote areas with limited access to electrical power. The performance of a hydraulic ram pump is influenced by several design and operating parameters, one of which is the configuration of the waste valve. However, studies investigating the effect of the number of waste valves on hydraulic ram pump performance remain limited. Therefore, this study aimed to investigate the effect of varying the number of waste valves on the water discharge and efficiency of a hydraulic ram pump. An experimental method was employed using three waste valve configurations, namely one, two, and three waste valves. The observed parameters included waste valve discharge, delivery discharge, total inlet discharge, and pump efficiency, which was calculated using the D'Aubuisson efficiency method. The results indicated that increasing the number of waste valves enhanced the hydraulic ram pump discharge. The average waste valve discharge increased from 17.75 L/s to 29.43 L/s and 46.27 L/s, while the average delivery discharge increased from 1.05 L/s to 2.10 L/s and 3.10 L/s. Similarly, the total inlet discharge increased from 18.80 L/s to 31.53 L/s and 49.37 L/s. The calculated efficiencies were 69.81% for the single waste valve configuration, 83.26% for the two-waste-valve configuration, and 78.49% for the three-waste-valve configuration. The decrease in efficiency observed with three waste valves indicates that increasing the number of waste valves does not necessarily improve pump performance due to higher energy losses during the water hammer generation process. Therefore, under the experimental conditions of this study, the two-waste-valve configuration provided the optimum performance by achieving the highest efficiency while maintaining a relatively high delivery discharge. Keywords: hydraulic ram pump, waste valve, number of waste valves, water discharge, D'Aubuisson efficiency, water hammer.